UPAYA PENINGKATAN KETERAMPILAN PRAKTIK UNTUK MENGOPTIMALKAN METODE EKSPERIMEN/NON-EKSPERIMEN PADA SISWA KELAS XII IPA-2 - JONI ALI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This study aims to improve student practical skills and student learning outcomes, as well as other aspects, through optimizing the use of experimental / non-experimental methods. There is also an increase in teacher creativity and renewal in the management of the biology learning process. This research was conducted at SMA Negeri 1 Batanghari, class XII IPA-2, with 29 students as research subjects. Through this research, it is hoped that teachers will be able to play a role as learning innovators. With the increased creativity of teachers in the implementation of learning activities with the experimental / non-experimental method, the difficulty of students in using laboratory tools / materials, analyzing pictures / diagrams / schemes according to the pictures on the Student Worksheet (LKS), can optimize the use of learning time. in achieving the expected learning objectives. The results showed that by optimizing the use of the experimental / non-experimental method, students' practical skills could improve (through the use of tools / materials, analyzing pictures / diagrams / schemes), and student learning outcomes, as well as other aspects (cheerfulness, enthusiasm, attention and activity).